2020
DOI: 10.11604/pamj.2020.37.78.25100
|View full text |Cite
|
Sign up to set email alerts
|

An elevated 8-isoprostaglandin F2 alpha (8-iso-PGF2α) in COVID-19 subjects co-infected with malaria

Abstract: Introduction the most recently discovered severe acute respiratory syndrome Coronavirus 2 (SARS-COV-2) that causes COVID-19, subjected the entire world in turmoil health-wise and economically. With higher burden of malaria in Nigeria and other sub-Saharan African countries coupled with fragile healthcare system and delivery, these may pose a threat in the diagnosis and management of COVID-19 patients co-infected with malaria. Free radicals have been implicated in the progression and pathogenesis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 7 publications
7
27
0
Order By: Relevance
“…We examined the full-texts of the remaining 385 articles, resulting in the exclusion of 375 articles due to the following reasons: 192 were review articles; 47 were commentaries, corrections, news items, letters to the editor, short reports, and communications; 43 were in vitro studies; 24 were about COVID-19 only, with non-relevant parameters; 16 were COVID-19 model predictions; 9 were conducted before 2019; 8 were molecular docking studies; 7 were non-relevant case reports; 6 were systematic and scoping reviews; 6 were community implementations; 5 were surveys; 5 were clinical trials related to COVID-19 treatment efficacy/safety but not associated with malaria; 4 were animal studies; 2 were cost-analytic studies; and 1 study reported the data of the same group of participants. After these exclusions, 10 studies [10][11][12][13][14][15][16][17][18][19] met the eligibility criteria and were included. An additional two studies [20,21] were retrieved from Google Scholar and included.…”
Section: Search Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We examined the full-texts of the remaining 385 articles, resulting in the exclusion of 375 articles due to the following reasons: 192 were review articles; 47 were commentaries, corrections, news items, letters to the editor, short reports, and communications; 43 were in vitro studies; 24 were about COVID-19 only, with non-relevant parameters; 16 were COVID-19 model predictions; 9 were conducted before 2019; 8 were molecular docking studies; 7 were non-relevant case reports; 6 were systematic and scoping reviews; 6 were community implementations; 5 were surveys; 5 were clinical trials related to COVID-19 treatment efficacy/safety but not associated with malaria; 4 were animal studies; 2 were cost-analytic studies; and 1 study reported the data of the same group of participants. After these exclusions, 10 studies [10][11][12][13][14][15][16][17][18][19] met the eligibility criteria and were included. An additional two studies [20,21] were retrieved from Google Scholar and included.…”
Section: Search Resultsmentioning
confidence: 99%
“…An additional two studies [20,21] were retrieved from Google Scholar and included. Thus, a final set of 12 studies [10][11][12][13][14][15][16][17][18][19][20][21] were included for qualitative and quantitative synthesis (meta-analysis) and analysis of co-infected cases. Among the 12 studies included, 5 [10][11][12][13]21] were original research articles, and 7 [14][15][16][17][18][19][20] were case reports or series (Fig 1).…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations